PENGARUH KOMUNIKASI TERHADAP DISIPLIN KERJA KARYAWAN PADA OJAS PRANA CAFE & RESTAURANT UBUD GIANYAR - Anak Agung Putu Swabawa; Made Setena; I Putu Budiarta; I Wayan Basi Arjana; I Dewa Gede Ari Pemayun (Warmadewa Management and Business Journal (WMBJ), 2024)
This study aims at the effectiveness of communication and the level of employee discipline as well as the effect of communication on employee work discipline at Ojas Prana Café & Restaurant Ubud Gianyar at Ojas Prana Cafe & Restaurant Ubud Gianyar. There are 5 methods used to collect data, namely: observation, interview, questionnaire, documentation, and literature study. The analysis technique used, namely: a. Quantitative Analysis, which is an analysis technique for analyzing quantitative data, where the analytical techniques used include 1) Simple Linear Regression Analysis, 2) Simple Correlation Analysis, 3) Determination Analysis. b. Descriptive analysis techniques to explain the results of the analysis and help draw conclusions about research results Based on the results of the analysis, it shows that the communication process in operations at Ojas Prana Cafe & Restaurant Ubud Gianyar is running very effectively. Work discipline in operations at Ojas Prana Cafe & Restaurant Ubud Gianyar is very good. Communication has a real or significant effect on employee work discipline at the Ojas Prana Café & Restaurant Ubud company which can be seen from t count (3.753) greater than t table (1.833), which is in the area of ​​rejection of Ho and Ha being accepted. The effect is very strong with a positive correlation coefficient of 0.781 which lies between 0.76 – 1.00 in the very strong criteria. While the influence relationship is positive, where with the improvement of communication one unit causes an increase in discipline of 0.958 units.